A multicentre randomised controlled trial assessing whether MRI-targeted biopsy is non-inferior to standard transrectal ultrasound guided biopsy for the diagnosis of clinically significant prostate cancer in men without prior biopsy: a study protocol. Issue 10 (12th October 2017) - Kasivisvanathan, Veeru; Jichi, Fatima; Klotz, Laurence; Villers, Arnauld; Taneja, Samir S; Punwani, Shonit; Freeman, Alex; Emberton, Mark; Moore, Caroline M
Abstract : Introduction: The classical pathway for the diagnosis of prostate cancer is transrectal ultrasound-guided (TRUS) biopsy of the prostate initiated on the basis of a raised prostate-specific antigen (PSA). An alternative pathway is to perform multi-parametricMRI (MPMRI) to localise cancer and to use this information to influence the decision for, and conduct of, a subsequent biopsy, known as an MPMRI-targeted biopsy. An MPMRI pathway has been shown to detect a similar or greater amount of clinically significant cancer as TRUS biopsy but has several advantages, including the potential to biopsy fewer men with fewer cores. Methods: This is a pragmatic, international, multicentre, parallel group randomised study in which men are allocated in a 1:1 ratio to an MPMRI or TRUS biopsy pathway. This study will assess whether an MPMRI-targeted biopsy approach is non-inferior to a standard TRUS biopsy approach in the diagnosis of clinically significant cancer. Men in the MRI arm will undergo targeted biopsy of suspicious areas only and no biopsy will be carried out if the MRI is non-suspicious. Men in the TRUS biopsy will undergo a standard 10–12-core TRUS biopsy. The main inclusion criteria are a serum PSA ≤20 ng/mL, a digital rectal examination finding of T2 or less and no prior prostate biopsy. The primary outcome is the proportion of men with clinically significant cancer detected. A sample size of at least 470 patients is required. Key secondary outcomes include the proportion of clinically insignificant cancer detected. Ethics and dissemination: Ethical approval was obtained from the National Research Ethics Committee East Midlands, Leicester (15/EM/0188). Results of this study will be disseminated through national and international papers. The participants and relevant patient support groups will be informed about the results of the study. Registration details: NCT02380027; Pre-results